2018
DOI: 10.1096/fj.201801594r
|View full text |Cite
|
Sign up to set email alerts
|

Genetic ablation of NFAT5/TonEBP in smooth muscle cells impairs flow‐ and pressure‐induced arterial remodeling in mice

Abstract: The arterial wall adapts to alterations in blood flow and pressure by remodeling the cellular and extracellular architecture. Biomechanical stress of vascular smooth muscle cells (VSMCs) in the media is thought to precede this process and promote their activation and subsequent proliferation. However, molecular determinants orchestrating the transcriptional phenotype under these conditions have been insufficiently studied. We identified the transcription factor, nuclear factor of activated T cells 5 (NFAT5; or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(24 citation statements)
references
References 65 publications
(73 reference statements)
1
23
0
Order By: Relevance
“…28 For VSMCs, our former studies showed that NFAT5 acts on the transcriptional level to promote the expression of biomechanical stress-regulated genes, which control the formation of focal adhesions and the organization of the cytoskeleton. 11 In fact, loss of Nfat5 impairs stress fiber formation as a prototypic stabilizing F I G U R E 4 Genetic ablation of Nfat5 and its effect on cholesterol-exposed VSMCs. Genetic ablation of Nfat5 was achieved by expressing Cre-recombinase in murine Nfat5 fl/fl VSMCs via adenoviral transduction (AdCre, an empty vector adenovirus (AdPl) served as control).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…28 For VSMCs, our former studies showed that NFAT5 acts on the transcriptional level to promote the expression of biomechanical stress-regulated genes, which control the formation of focal adhesions and the organization of the cytoskeleton. 11 In fact, loss of Nfat5 impairs stress fiber formation as a prototypic stabilizing F I G U R E 4 Genetic ablation of Nfat5 and its effect on cholesterol-exposed VSMCs. Genetic ablation of Nfat5 was achieved by expressing Cre-recombinase in murine Nfat5 fl/fl VSMCs via adenoviral transduction (AdCre, an empty vector adenovirus (AdPl) served as control).…”
Section: Discussionmentioning
confidence: 99%
“…Along these lines, our former studies identified NFAT5 as a mechanoresponsive transcription factor that is activated by biomechanical stress 8 to support cytoskeletal reorganization, VSMC migration, 9 and proliferation. 11 As such, NFAT5 may adapt the VSMC phenotype to a potential harmful environmental stress, but nevertheless, promote responses contributing to detrimental vascular remodeling processes such as hypertension-induced arterial thickening. 11 Here, we revealed that NFAT5 is not promoting, but is rather preventing, a potentially harmful accumulation of lipids in VSMCs that may contribute to the formation of complex arteriosclerotic lesions in the long run.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The role of NFAT5 in arterial wall remodelling was also studied by using an inducible smooth muscle cell (SMC)-specific Nfat5 knockout mouse model [ 94 ]. In cultured mouse VSMCs, loss of the Nfat5 gene inhibited the expression of gene sets involved in controlling the cell cycle, and the interaction with the extracellular matrix and cytoskeletal dynamics.…”
Section: Nfat5 Signalling In Cardiovascular Dysfunctionmentioning
confidence: 99%
“…However, proliferation of VSMCs and the thickening of the arterial wall wee inhibited during both flow-induced collateral remodelling and hypertension-mediated arterial hypertrophy. These findings identify NFAT5 as a novel molecular determinant of biomechanically induced phenotype changes in VSMCs and wall stress-induced arterial remodelling processes [ 94 ].…”
Section: Nfat5 Signalling In Cardiovascular Dysfunctionmentioning
confidence: 99%